Management of Autoimmune Encephalitis: An Observational Monocentric Study of 38 Patients - Macher, Stefan; Zimprich, Friedrich; De Simoni, Desiree; Höftberger, Romana; Rommer, Paulus S. (Frontiers in Immunology, 2018)
The emerging field of autoimmune encephalitis has gained importance over the last years in neurology. The broad field of symptoms and syndromes poses a great challenge in diagnosis for clinicians. Most important in the management of AIE is early diagnosis and based on it the appropriate treatment. Advances in neuroimmunology have elucidated pathophysiological concepts and treatment opportunities. Based on experiences from real word data from our clinic we compare demographics, diagnostics, treatment options and outcomes with knowledge from literature. We present 36 patients suffering from autoimmune encephalitis (antibodies were detected against NMDAR in seven patients, against LGI1 in 6 patients, against GAD in 5 patients, CASPR2, IGLON5, YO, Glycin in 3 patients, CV2 in 2 patients, and Ma2 and AMPAR in 1 patients). Our data and outcomes are comparable with data from literature. How long treatment after an acute relapse should be performed is a matter of debate. In contrary to other experts in the field we stop treatment and monitor patients very closely after tumor removal and after rehabilitation from first attack.